Multiple Step Interlaced Beam Scan to Minimize the Deviation of Radar Detection Performance - Yoon, Ji Hwan; Park, Yeonhee; Roh, Ji Eun; Park, Sung Chul (Journal of Electromagnetic Engineering and Science, 2020)
For detection of targets, a radar conventionally scans a specified search volume with a fixed beam lattice of a specified beam spacing. With the fixed beam lattice, the detection performance of the radar within a unit beam lattice changes depending on the line-of-sight angle to a target. In this paper, multiple step interlaced scan is proposed to minimize the deviation of the detection performance due to the change of the target line-of-sight angle. As a figure of merit for the detection performance, the cumulative probability of detection is analyzed for various values of the interlaced scan step with different beam overlap ratios, and the optimal values of the steps to minimize the deviation of the cumulative probability of detection are derived.